Local polarization in oxygen-deficient LaMnO_{3} induced by charge localization in the Jahn-Teller distorted structure - Chiara Ricca; Nicolas Niederhauser; Ulrich Aschauer (Physical Review Research, 2020)
The functional properties of transition metal perovskite oxides are known to result from a complex interplay of magnetism, polarization, strain, and stoichiometry. Here, we show that for materials with a cooperative Jahn-Teller distortion, such as LaMnO_{3} (LMO), the orbital order can also couple to the defect chemistry and induce novel material properties. At low temperatures, LMO exhibits a strong Jahn-Teller distortion that splits the e_{g} orbitals of the high-spin Mn^{3+} ions and leads to alternating long, short, and intermediate Mn-O bonds. Our DFT+U calculations show that, as a result of this orbital order, the charge localization in LMO upon oxygen vacancy formation differs from other manganites, such as SrMnO_{3}, where the two extra electrons reduce the two Mn sites adjacent to the vacancy. In LMO, relaxations around the defect depend on which type of Mn-O bond is broken, affecting the d-orbital energies and leading to asymmetric and hence polar excess-electron localization with respect to the vacancy. Moreover, we show that the Mn-O bond lengths, the orbital order, and consequently the charge localization and polarity are tunable via strain.